Age-Dependent Switch of the Role of Serotonergic 5-HT1A Receptors in Gating Long-Term Potentiation in Rat Visual Cortex In Vivo. (10th May 2016) - Gagolewicz, Peter J.; Dringenberg, Hans C.
Abstract : The rodent primary visual cortex (V1) is densely innervated by serotonergic axons and previous in vitro work has shown that serotonin (5-HT) can modulate plasticity (e.g., long-term potentiation (LTP)) at V1 synapses. However, little work has examined the effects of 5-HT on LTP under in vivo conditions. We examined the role of 5-HT on LTP in V1 elicited by theta burst stimulation (TBS) of the lateral geniculate nucleus in urethane-anesthetized (adult and juvenile) rats. Thalamic TBS consistently induced potentiation of field postsynaptic potentials (fPSPs) recorded in V1. While 5-HT application (0.1–10 mM) itself did not alter LTP levels, the broad-acting 5-HT receptor antagonists methiothepin (1 mM) resulted in a clear facilitation of LTP in adult animals, an effect that was mimicked by the selective 5-H T 1 A receptor antagonist WAY 100635 (1 mM). Interestingly, in juvenile rats, WAY 100635 application inhibited LTP, indicative of an age-dependent switch in the role of 5-H T 1 A receptors in gating V1 plasticity. Analyses of spontaneous electrocorticographic (ECoG) activity in V1 indicated that the antagonist-induced LTP enhancement was not related to systematic changes in oscillatory activity in V1. Together, these data suggest a facilitating role of 5-H T 1 A receptor activation on LTP in the juvenile V1, which switches to a tonic, inhibitory influence in adulthood.